Packet scheduling method for streaming multimedia data - Kang, Sang Hyuk (2008)
The present invention relates, in general, to streaming technology and, more particularly, to a packet scheduling method for streaming multimedia data. The packet scheduling method of the present invention streams multimedia data by a server in a network. The network includes the server for providing multimedia data divided into picture groups each having a sequence of N pictures, and a terminal for displaying the multimedia data received from the server in a streaming manner. In the packet scheduling method, the sequences of the pictures are divided into motion part packets and texture part packets, and priorities are assigned to the packets according to temporal scaling. A threshold for a predetermined priority is determined in consideration of conditions of a channel and a buffer status of the terminal and a substream is constructed using packets with priorities below the threshold within the respective picture groups. The packets in the constructed substream are sequentially transmitted to the terminal.